Hypoactive–hypoalert behaviour and thalamic hypometabolism due to intracranial hypotension. Issue 4 (22nd April 2017) - Kearney, Seamus; Flynn, Peter; Hughes, Simon; Spence, Wendy; McCarron, Mark Owen
Abstract : A 47-year-old man presented with a 9-year history of a hypoalert hypoactive behaviour syndrome, caused by the deep brain swelling variant of spontaneous intracranial hypotension. Along with apathy with retained cognition, he had stable ataxia, impaired upgaze and episodes of central apnoea. MRI brain showed a sagging brainstem, pointed ventricles and reduced angle between the vein of Galen and the straight sinus, but no meningeal enhancement or subdural collections. A dopamine transporter scan showed preganglionic dopamine receptor deficiency; a fluorodeoxy glucose positron emission tomography scan showed bilateral hypothalamic hypometabolism. This variant of spontaneous intracranial hypotension may alter deep brain functioning within the basal ganglia and thalamus, causing the hypoactive-hypoalert behaviour phenotype.